Proposal for an Educational Program for the Prevention of Complications of Polycystic Ovary Syndrome - Edison Sotalin Nivela; Lexter Michalache Bernal; María de Lourdes Llerena Cepeda (Medisur)
Foundation: polycystic ovary syndrome is characterized by hyperandrogenism and oligoovulation. It affects women of reproductive age and can have serious health implications. Objective: to design a proposal for an educational program to achieve the prevention of complications of polycystic ovary syndrome in Ecuadorian women. Method: a descriptive, pedagogical research was developed at the Regional Autonomous University of the Andes between July and January 2022. The variables were used: topics, objectives, methods and means, and form of evaluation. For the development of this study, three phases or stages were followed: bibliographic review, development of an educational program and evaluation of the proposal by specialists. Results: the contents with which the educational program was developed were determined: Female Hormonal Health: Preventing Polycystic Ovary Syndrome, aimed at Ecuadorian women. The program was made up of 5 sessions, with specific objectives and content. The methods in each session were similar; The proposed evaluation consisted of a pre- and post-program evaluation, as well as patient follow-up and a satisfaction survey. Conclusions: a proposed educational program on polycystic ovary syndrome for Ecuadorian women was developed. This program can be implemented in Primary Care health centers to increase the level of knowledge about this condition, promote healthy lifestyles and habits, and help women take preventive measure.